Ketamine attenuates endotoxin-induced leukocyte adherence in rat mesenteric venules - Schmidt, Heinfried; Ebeling, Dorothea; Bauer, Harald; Bach, Alfons; Böhrer, Hubert; Gebhard, Martha-Maria; Martin, Eike (Critical care medicine, 1995)
Objectives - To determine the influence of ketamine on endotoxin-induced leukocyte adherence and venular microhemodynamics. - Design - Randomized, controlled trial. - Setting - Experimental laboratory. - Subjects - Thirty male Wistar rats. - Interventions - The rats were pretreated with ketamine (10 mg/kg iv) or 0.9% saline, and both groups were given endotoxin (Escherichia coli lipopolysaccharide; 5 mg/kg iv). The control group received two doses of 0.9% saline. - Measurements and Main Results - The rates of leukocyte adherence and changes in microhemodynamics were monitored in rat mesenteric venules, using in vivo video microscopy. The number of adherent leukocytes was determined on-line in 10-min intervals from 60 mins before until 2 hrs after endotoxin administration. Venular diameters, red blood cell velocity, volumetric blood flow, and the venular wall shear rate were monitored before and at 10, 30, and 60 mins after endotoxin exposure. - A 6.3-fold increase in the number of adherent leukocytes was observed 10 mins after administration of endotoxin when compared with control animals (5.87 plus minus 0.69 vs. 0.93 plus minus 0.21 adherent cells/100 micro meter; p less than .001). This increase remained unchanged for 120 mins. In ketamine-pretreated rats, a 2.6-fold increase in leukocyte adherence occurred during the first 20 mins after endotoxin exposure (2.40 plus minus 0.46 vs. 0.93 plus minus 0.21 adherent cells/100 micro meter; p less than .01). However, no difference in the number of adherent leukocytes between ketamine-pretreated and control animals was found after this 20-min period. In animals of the control group, no increase in leukocyte adherence occurred during the entire observation time. Diameters of mesenteric venules did not change after endotoxin exposure in any of the groups. Red blood cell velocity and venular blood flow in the endotoxin-treated groups decreased 10 mins after the injection of endotoxin when compared with controls, but these values did not show any difference when they were compared between ketamine and saline-pretreated animals. Similarly, venular wall shear rate in the endotoxin-treated groups decreased 10 and 30 mins after injection of endotoxin. However, no significant difference occurred between ketamine and saline-pretreated animals. - Conclusions - Pretreatment with ketamine attenuates endotoxin-induced leukocyte adherence by a shear rate-independent mechanism, suggesting reduced expression of adhesion molecules. These results indicate that ketamine exerts an anti-inflammatory effect, which might be beneficial in septic patients. - (Crit Care Med 1995; 23:2008-2014)
Gesehen am 21.11.2023